De Garengeot hernia: laparoscopic treatment in emergency - Rollo, Alessio; Franzini, Christian; Casali, Lorenzo; Santi, Caterina; Lombardo, Eugenio; Violi, Vincenzo (Acta Biomedica Atenei Parmensis, 2019)
Introduction: De Garengeot Hernia is described as the presence of an appendix within a femoral hernia. Case Report: We report the case of an elderly woman, who presented with incarcerated femoral hernia without signs of bowel obstruction. CT showed a femoral hernia with appendix in the femoral canal with signs of strangulation. the patient underwent emergency surgery. Diagnostic laparoscopy revelead a non-reducible appendix in the femoral canal, in the absence of signs of peritonitis. An infrainguinal incision was performed. An gangrenous appendix within the sac was revealed, detached from the sac and reintroduced into the abdomen through the femoral canal. The laparoscopic appendectomy was then performed. The hernia repair was performed by suturing the iliopubic tract to Cooper’s ligament. Patient had a regular course. Discussion: De Garengeot’s hernia is a rare occurrence. After the year 2000 a total of 32articles, wich presented 34 cases of de Garengeot’s hernia have been published. Due to the rarity of this disease there is not standard procedure; laparoscopy may be a valid technique for determining the condition of the hernia, but due to the difficulty of preoperative diagnosis it is unlikely to be the first choice for the surgical approach. The use of CT can therefore be decisive to help the surgeon in the choice of the approach. Conclusion: De Garengeot’s hernia can be approached in urgent laparoscopy even in the complicated forms of appendicular inflammation. (www.actabiomedica.it)